Level of Self Esteem Among Medical Students in International Islamic University Malaysia Kuantan (IIUM) and Its Association With Religiosity - Amirah Amiruddin; Nurul Fitri Mustapa; Azwanis Abdul Hadi; Muhammad ‘Adil Zainal Abidin (USIM Press, 2024)
Vol. 33 No. 2 (2021): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences [August 2021]